1977
DOI: 10.1002/hlca.19770600110
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Cycloalkenes by the Intramolecular Wittig Reaction

Abstract: A simple synthesis of a series of bicyclo[m.n.0]‐1‐alkenes (m, n = 3,4,5) from 2‐oxocycloalkanecarboxylates by the intramolecular Wittig reaction is reported (see p. 70–72). The spectral properties (IR., 1H‐NMR. and 13C‐NMR.) of these annulated trisubstituted olefins are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 79 publications
1
18
0
1
Order By: Relevance
“…[54,55] The X-ray structure of 4[SbF 6 ] ( Figure 2) revealed that the gold center adopts an essentially linear coordination geometry with a C (carbene) -Au-(-C≡C-centroid ) angle of 176.7°. The Au-C(carbene) and Au-(-C≡C-centroid ) distances are 2.012 (4) 6 ], they were also synthesized via independent routes using authentic free alkenes bicyclo [3.3.0]oct-1(5)-ene (2) [56,57] and cis-bicyclo-[3.3.0]oct-2-ene (3) [58] (prepared following literature procedures), and (IPr)AuSbF 6 6 ] are rotated by about 79°(average) relative to the carbene Au(N-C-N) planes whereas in 6[SbF 6 ], this angle is about 74°. The structurally authenticated alkenes adducts of (IPr)Au + show a range of such inter-planar angles from essentially coplanar to nearly perpendicular suggesting that the relative alkene orientation is determined largely by steric factors, [37] presumably arising from interaction with methyl hydrogens on the IPr ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[54,55] The X-ray structure of 4[SbF 6 ] ( Figure 2) revealed that the gold center adopts an essentially linear coordination geometry with a C (carbene) -Au-(-C≡C-centroid ) angle of 176.7°. The Au-C(carbene) and Au-(-C≡C-centroid ) distances are 2.012 (4) 6 ], they were also synthesized via independent routes using authentic free alkenes bicyclo [3.3.0]oct-1(5)-ene (2) [56,57] and cis-bicyclo-[3.3.0]oct-2-ene (3) [58] (prepared following literature procedures), and (IPr)AuSbF 6 6 ] are rotated by about 79°(average) relative to the carbene Au(N-C-N) planes whereas in 6[SbF 6 ], this angle is about 74°. The structurally authenticated alkenes adducts of (IPr)Au + show a range of such inter-planar angles from essentially coplanar to nearly perpendicular suggesting that the relative alkene orientation is determined largely by steric factors, [37] presumably arising from interaction with methyl hydrogens on the IPr ligand.…”
Section: Resultsmentioning
confidence: 99%
“…[66] and was dried using 4 Å molecular sieves (see below as well). (IPr)AuCl, [54] (IPr)AuCl 3 , [67] [(SIPr)Au(cyclooctyne)][SbF 6 ], [25] and AgNTf 2 , [68] bicyclo [3.3.0]oct-1(5)-ene, [56,57,69] and cis-bicyclo [3.3.0]oct-2-ene [58] were prepared according to reported procedures. AgSbF 6 was purchased from commercial sources and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…82 (1999) The preparation of the corresponding phosphonium salt from 7 turned out to be a crucial step in this synthesis, since various commonly applied methods to substitute the primary bromide by PPh 3 failed. In solvents like benzene, toluene [13] or Et 2 O at elevated temperature (general method for the synthesis of (oxoalkyl)triphenylphosphonium bromide [14]), only tarry materials were recovered. However, melting at 858 a neat mixture of bromide 7 and PPh 3 (prepared by dissolving both components in abs.…”
mentioning
confidence: 99%
“…Die den Geruchscharakter des atherischen 01s von Opoponax bestimmende Verbindung erwies sich als (+)-(S,Z)-a -Bisabolen[37]. Fur die racemische Form der Stereoisomeren des CI -Bisabolens ist eine rationelle Synthese bekanntgeworden[38]. (-)-a -Bisabolol35, u. a. als Hauptprodukt des deutschen Kamillen-01s (45 "0) bekannt, tragt dort zur antiphlogistischen und spasmolytischen Aktivitat des atherischen 01s bei und fallt durch seinen angenehmen blumigen Geruch auf.…”
unclassified